Increased cleavage of von Willebrand factor by ADAMTS13 may contribute strongly to acquired von Willebrand syndrome development in patients with essential thrombocythemia - Kubo, Masayuki; Sakai, Kazuya; Hayakawa, Masaki; Kashiwagi, Hirokazu; Yagi, Hideo; Seki, Yoshinobu; Hasegawa, Atsushi; Tanaka, Haruyuki; Amano, Itsuto; Tomiyama, Yoshiaki; Matsumoto, Masanori (Journal of thrombosis and haemostasis, 2022)
Background Patients with essential thrombocythemia (ET) often experience bleeding associated with acquired von Willebrand syndrome (AVWS) when the platelet count is markedly increased. Objective We investigated whether von Willebrand factor (VWF) degradation is enhanced in patients with ET. Methods Seventy patients with ET underwent VWF multimer (VWFM) analysis and measurement of VWF‐related parameters. We calculated the VWFM index, defined as the ratio of intensities of a patient's molecular weight‐categorized VWFMs, and those of a healthy subject's, using densitometric analysis. VWF degradation product (DP) was measured via ELISA using a monoclonal antibody that specifically recognizes Y1605 at the C‐terminal boundary, which is exposed following ADAMTS13‐mediated cleavage of the Y1605‐M1606 bond of the VWF A2 domain. Results Patients with higher platelet counts had a significantly reduced high molecular weight (HMW)‐VWFM index and an increased VWF‐DP:VWF antigen (Ag) ratio compared to those with lower platelet counts. On multivariate analysis, the VWF‐DP/VWF:Ag ratio was an independent predictor of the HMW‐VWFM index. Patients who underwent cytoreductive therapy had a significantly higher HMW‐VWFM index and lower VWF‐DP/VWF:Ag ratio than those who did not. Among individual patients, there was also a significant increase in the HMW‐VWFM index and a decrease in the VWF‐DP/VWF:Ag ratio after cytoreductive therapy compared to pre‐therapy values. Conclusion In patients with ET, an increased platelet count is associated with enhanced cleavage of VWF at the Y1605‐M1606 bond, primarily by ADAMTS13, leading to AVWS. Cytoreductive therapy reduces the platelet count, prevents excessive VWF cleavage, and improves VWFM distributions.